Criteria to Distinguish Between Periglacial, Proglacial and Paraglacial Environments - Slaymaker, Olav (Quaestiones Geographicae, 2011)
Clarification of the differences between the terms periglacial, proglacial and paraglacial is based on consideration of their conventional definitions, and noting that the term "periglacial" is a function of process, "proglacial" is a function of location and "paraglacial" is a function of degree and mode of recovery from the disturbance of continental glaciation. Periglacial and proglacial environments are commonly viewed as being adjusted to contemporary process, though important questions have been raised about relict periglacial landscapes in this regard. Paraglacial environments are explicitly out of adjustment with contemporary process and retain in their configuration a glacial signature. All three concepts are seen to be essential to comprehensive understanding of glaciated environments. It is a nested set of concepts which overlap in the field but none of the terms is redundant. Criteria for differentiation of these cold environment descriptors are proposed.